(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The Armenian highlands are characterized by the presence of potentially seismic zones that form the level of seismic hazard in the territory of the RA. In particular, the Van earthquake (M=7.2) in October 23, 2011 manifested in Yerevan by seismic shaking (J=5–6 points). The article presents the analysis of the seismic-geodyna-mic situation of the study area during the preparation of this strong earthquake. The first stage of the analysis is devoted to the study of low seismicity (M<4.0) of the region with coordinates (φºN 38.0–42.0; λºE 42.0–48.0) for the time period 2004–2011. Year-to-year maps of the spatio-temporal distribution of earthquake epicen-ters for the period 2004–2011 were built for 2 groups of basic data – seismic events with (M<2.5) and (2.5≤M<4.0). It turned out that in the southwestern part of the study area (Van focal zone), weak earthquakes (M<4.0) in 2004–2009 were not recorded. Their number increased sharply in the period of 01.01.2010–23.10.2011.